Steric and stereoscopic disulfide construction for cross-linkage via N-dithiophthalimides. Issue 15 (1st April 2020) - Gao, Wen-Chao; Tian, Jun; Shang, Yu-Zhu; Jiang, Xuefeng
Abstract : A series of steric and stereoscopic disulfides are constructed with N -dithiophthalimides, enabling the cross-linkage of biomolecules, drugs and fluorescent molecules. Abstract : Disulfide bonds are a significant motif in life and drug-delivery systems. In particular, steric hindrance and stereoscopic disulfide linkers are closely associated with the stability of antibody–drug conjugates, which affects the potency, selectivity, and pharmacokinetics of drugs. However, limited availability and diversity of tertiary thiols impede the construction of steric and stereoscopic disulfides for cross-linkage in biochemistry and pharmaceuticals. Through modulating the mask effect of disulfurating reagents, we develop a facile and robust strategy for construction of diverse steric and stereoscopic disulfides via N -dithiophthalimides. The practical cross-linkage of biomolecules including amino acids, saccharides, and nucleosides with different drugs and fluorescent molecules is successfully established through hindered disulfide linkers.